New technologies and procedures for cervical cancer screening - Cuzick, Jack; Knebel Doeberitz, Magnus von (Vaccine, 2012)
The clearly higher sensitivity and reproducibility of human papillomavirus (HPV) DNA testing for highgrade cervical intraepithelial neoplasia (CIN) has led to widespread calls to introduce it as the primary screening test. The main concern has been its lower speciﬁcity, due to the fact that it cannot separate transient from persistent infections, and only the latter are associated with an increased risk of high-grade CIN and cancer. Thus, even proponents of HPV testing generally only recommend it for women over the age of 30 years (or in some cases 35 years). If HPV testing is to reach its full potential, new approaches with better speciﬁcity are needed, either as triage tests for HPV positive women or, if the high sensitivity of HPV DNA testing can be maintained, as alternate primary screening modalities. Approaches that may useful in this regard, especially as triage tests, include HPV typing, methylation (and consequent silencing) of host and viral genes, and new cytologic methods, such as p16INK4a staining, which attempt to identify proliferating cells. At an earlier stage of development are direct methods based on detection of HPV E6 or E7 proteins. Recent progress and current status of these methods is discussed in this chapter. The current status of visual inspection (VIA and VILI) methods is also surveyed and progress on self-sampling is reviewed.